Effect of electron beam irradiation and poly(vinyl pyrrolidone) addition on mechanical properties of polycaprolactone with empty fruit bunch fiber (OPEFB) composite - Ibrahim, Nor Azowa; Ahmad, S. N. A.; Wan Yunus, Wan Md. Zin; Mohd Dahlan, Khairul Zaman (Budapest University of Technology, 2009)
Biodegradable composites or green composites were prepared by melt blending technique using polycaprolactone and oil palm empty fruit bunch fibre (OPEFB). Since OPEFB is not compatible with PCL a binder, poly(vinyl pyrrolidone), (PVP) was used to improve the interaction between PCL and OPEFB. The composites produced were irradiated using electron beam to improve the mechanical properties. The tensile, flexural and impact strengths of PCL/OPEFB composites were improved by addition of 1% by weight of PVP and irradiated with 10 kGy of electron beam. The FTIR spectra indicate a slight increase of frequencies at C=O peaks from 1730 to 1732 cm–1 after irradiation indicates some interaction between C=O and O–H. The surface morphology of the facture surface obtained from tensile test shows no fibre pull out indicating good adhesion between the OPEFB and PCL after addition of PVP.